Political Implications in China-Latin America Relations: sian Consensus as a Network of Global Power and the Brazilian Case - Vadell, Javier A. (2014)
This paper analyzes the People’s Republic of China economic and political ascendance in the 21st century, focusing on the evolution of its sui géneris economic development model and its significance for the relationship between China and the developing countries of the peripheral ‘Global South.’ The objective of this article is to analyze the relationship between China and Latin America in the 21st century, characterizing it as a new Center-periphery global power network based on trade and investment, which is often referred to as the ‘Asian Consensus’. The article will give special attention to the Brazilian case.